A fatoração de argumentos verbais no PB - Leticia Lucinda Meirelles (2018)
In this thesis, we take as study object the phenomenon denominated factoring of verb arguments in Brazilian Portuguese. This phenomenon occurs in pairs of sentences that constitute alternate forms of expressing the same verb argument: in a single syntactic constituent (unfactored form), or in two distinct constituents (factored form), as in the sentences as palhaçadas do palhaço divertiram as crianças the clown's antics amused the children/o palhaço divertiu as crianças com suas palhaçadas the clown amused the children with his antics. The unfactored and factored forms of the sentences establish a relation of paraphrase between them. Therefore, factoring of verb arguments is characterized by the discontinuity of the thematic role attributed to the complex argument, such as as palhaçadas do palhaço the clowns antics. Together with other works on the Syntax- Lexical Semantics Interface, we assume that the semantic properties of the verbs determine their participation in verb alternations. We assume as theoretical reference the proposal that Theta Roles are a group of semantic properties entailed by a predicate in a compositional way. This proposal is based on Dowty (1991) and on Franchi (2003 [1997]), being first presented in Cançado (2005) and reviewed in Cançado and Amaral (2016). We conclude that the factoring of verb arguments is a very broad syntactic-semantic phenomenon in BP that gives rise to different types of verb alternations. All alternations have in common the fact that they are pragmatically motivated and the fact that the factored verb argument is composed by a complex NP, which is formed by a type of nominal predication. However, each type of alternation has specific semantic constraints. In each factoring of verb arguments, these constraints allow us to group verbs into coarse-grained classes.